Affordable Three-Dimensional Printed Heart Models - Gómez-Ciriza, Gorka; Gómez-Cía, Tomás; Rivas-González, José Antonio; Velasco Forte, Mari Nieves; Valverde, Israel (Frontiers in Cardiovascular Medicine, 2021)
This is a 7-year single institution study on low-cost cardiac three-dimensional (3D) printing based on the use of free open source programs and affordable printers and materials. The process of 3D printing is based on several steps (image acquisition, segmentation, mesh optimization, slicing and three-dimensional printing). The necessary technology and the processes to set up an affordable three dimensional printing laboratory is hereby described in detail. Their impact on surgical and interventional planning, medical training, communication with patients and relatives, patient’s perception on care and new cardiac devices development was analyzed. 138 low-cost heart models were designed and printed from 2013 to 2020. All of them were from different Congenital Heart Disease patients . The average time for segmentation and design of the hearts was 136 minutes, the average time for printing and cleaning the models was 13.5 hours. The average production cost of the models was 85.7 € per model. This is the most extensive series of 3D printed cardiac models published to date. In this study, the possibility of manufacturing three dimensional printed heart models in a low cost facility fulfilling the highest requirements from a technical and clinical point of view is demonstrated.